A Contrastive Stylistic Study of Some Selected Commercial Advertisements in English and Arabic - Mahmood, Sahira Ahmed (Al-Adab Journal, 2021)
Publication is only one of the tools used by public relations, like advertising is one-way communication. Advertising , as a tool, has a great importance and influence in various business processes. It is a means of communication that based on the influence of one or more individuals; by the use of one of the means of promotion available to build communication between consumers and products; advertising is the method used by the trader to effect the buyer. A range of non-personal communication means and methods ; to convey ideas and promote products and services. The Declaration is an important means of media used by different enterprises to communicate with the public and the target customers of their business; so that , to advertise great importance in the work environment. Advertising or publicity is an indispensable information activity for economic activities such as industry, trade, services and other economic activities, as well as for charitable and non-profit organizations and organizations, without announcing their efforts, they will not receive the social and financial support necessary to continue their work and performance of their mission. The aims of this paper are to examine and identify the aspects of advertisements and to clarify the linguistic features by explaining all issues which are related to it with examples and giving a detailed account about the grammatical issue of ‘A linguistic study of advertisement in English and Arabic’ hoping to would be more interesting for English students and those who are specialized in English linguistics.